Lived Experiences of Adolescent Mothers Attending Mbale Regional Referral Hospital: A Phenomenological Study - Violet Chemutai; Julius Nteziyaremye; Gabriel Julius Wandabwa (Hindawi Limited, 2020)
Background. Adolescence is a period of transition from childhood to adulthood, and is a critical stage in ones' development. It is characterized by immense opportunities and risks. By 2016, 16% of the world's population was of adolescents, with 82% residing in developing countries. About 12 million births were in 15-19 year olds. Sub-Saharan Africa, particularly East Africa, has high adolescent pregnancy rates, as high as 35.8% in eastern Uganda. Maternal mortality ratio (MMR) attributable to 15-19 years olds is significant with 17.1% of Uganda's MMR 336/100.000 live births being in this age group. Whereas research is awash with contributing factors to such pregnancies, little is known about lived experiences during early motherhood. This study reports the lived experiences of adolescent mothers attending Mbale Hospital. Materials and Methods. A phenomenological study design was used in which adolescent mothers that were attending Young Child Clinic were identified from the register and simple random sampling was used to select participants. We called these mothers by way of phone numbers and asked them to come for focus group discussions that were limited to 9 mothers per group and lasting about 45 minutes-1 hour. Ethical approval was sought and informed written consent obtained from participants. At every focus group discussion, the data which had largely been taken in local languages was transcribed and translated verbatim into English. Results. The research revealed that adolescent mothers go through hard times especially with the changes of pregnancy and fear of unknown during intrapartum and immediate postpartum period and are largely treated negatively by family and other community members in addition to experiencing extreme hardships during parenting. However, these early mothers' stress is alleviated by the joy of seeing their own babies. Conclusion. Adolescent motherhood presents a high risk group and efforts to support them during antenatal care with special adolescent ANC clinics and continuous counseling together with their household should be emphasized to optimize outcome not only during pregnancy but also thereafter. Involving these mothers in technical courses to equip them with skills that can foster self-employment and providing support to enable them pursue further education should be explored.